Dose escalation in advanced floor of the mouth cancer: a pilot study using a combination of IMRT and stereotactic boost - Blažek, Tomáš; Zděblová Čermáková, Zuzana; Knybel, Lukáš; Hurník, Pavel; Štembírek, Jan; Resová, Kamila; Paračková, Tereza; Formánek, Martin; Cvek, Jakub; Soumarová, Renata (Radiation oncology (London, England), 2021)
PURPOSE: We evaluated the efficiency and toxicity of stereotactic hypofractionated boost in combination with conventionally fractionated radiotherapy in the treatment of advanced floor of the mouth cancer. METHODS: Thirty-seven patients with advanced stage of the floor of the mouth cancer, histologically confirmed squamous cell carcinoma (p16 negative) ineligible for surgical treatment, were indicated for radiochemotherapy or hyperfractionated accelerated radiotherapy (HART). The radiotherapy protocol combined external beam radiotherapy (EBRT) and a stereotactic hypofractionated boost to the primary tumor. The dose delivered from EBRT was 70-72.5 Gy in 35/50 fractions. The hypofractionated boost followed with 10 Gy in two fractions. For the variables-tumor volume, stage and grade a multivariate analysis was performed to find the relationship between overall survival, local progression and metastasis. Toxicity was evaluated according to CTCAE scale version 4. RESULTS: After a median follow-up of 16 months, 23 patients (62%) achieved complete remission. The median time to local progression and metastasis was 7 months. Local control (LC) at 2 and 5-years was 70% and 62%, respectively. Progression-free survival (PFS) and overall survival (OS) were 57% and 49% at 2 years and 41% and 27% at 5 years, respectively. Statistical analysis revealed that larger tumors had worse overall survival and a greater chance of metastasis. Log-Rank GTV > 44 ccm (HR = 1.96; [95% CI (0.87; 4.38)]; p = 0.11). No boost-related severe acute toxicity was observed. Late osteonecrosis was observed in 3 patients (8%). CONCLUSION: The combination of EBRT and stereotactic hypofractionated boost is safe and seems to be an effective option for dose escalation in patients with advanced floor of the mouth tumors who are ineligible for surgical treatment and require a non-invasive approach.
Keywords: dospělí; Carcinoma, Squamous Cell; tumor burden; Dose Fractionation, Radiation; Female; Feasibility Studies; kombinovaná terapie; Adult; ženské pohlaví; Floor of the mouth tumor; frakcionace dávky záření; Stereotactic radiotherapy; lidé; Tumor Burden; Pilot Projects; Mouth Neoplasms; pilotní projekty; Aged, 80 and over; následné studie; Hypofractionated boost; Oral cavity tumor; radiochirurgie; Radiosurgery; nádory úst; studie proveditelnosti; Follow-Up Studies; progrese nemoci; Combined Modality Therapy; Aged; Czech Republic; spinocelulární karcinom; Male; Disease Progression; chemoradioterapie; Česká republika; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; CyberKnife; radioterapie s modulovanou intenzitou; Radiotherapy, Intensity-Modulated; Middle Aged; Chemoradiotherapy; CyberKnife boost; Humans